Nano-Neurotheranostics: Impact of Nanoparticles on Neural Dysfunctions and Strategies to Reduce Toxicity for Improved Efficacy - Vinod, Chiluka; Jena, Srikanta (Frontiers in Pharmacology, 2021)
Nanotheranostics is one of the emerging research areas in the field of nanobiotechnology offering exciting promises for diagnosis, bio-separation, imaging mechanisms, hyperthermia, phototherapy, chemotherapy, drug delivery, gene delivery, among other uses. The major criteria for any nanotheranostic-materials is 1) to interact with proteins and cells without meddling with their basic activities, 2) to maintain their physical properties after surface modifications and 3) must be nontoxic. One of the challenging targets for nanotheranostics is the nervous system with major hindrances from the neurovascular units, the functional units of blood-brain barrier. As blood-brain barrier is crucial for protecting the CNS from toxins and metabolic fluctuations, most of the synthetic nanomaterials cannot pass through this barrier making it difficult for diagnosing or targeting the cells. Biodegradable nanoparticles show a promising role in this aspect. Certain neural pathologies have compromised barrier creating a path for most of the nanoparticles to enter into the cells. However, such carriers may pose a risk of side effects to non-neural tissues and their toxicity needs to be elucidated at preclinical levels. This article reviews about the different types of nanotheranostic strategies applied in nervous dysfunctions. Further, the side effects of these carriers are reviewed and appropriate methods to test the toxicity of such nano-carriers are suggested to improve the effectiveness of nano-carrier based diagnosis and treatments.